Combination Application

Given the sequence a n = 6 n + 8 n { a }_{ n }={ 6 }^{ n }+{ 8 }^{ n } (for positive integers n n ), what is the remainder of a 83 { a }_{ 83 } upon division by 49 ? 49?


The answer is 35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Stilijan Nanovski
Nov 14, 2018

Since we are searching for the remainder upon dividing by 49, we will rewrite our expression as following:

a 83 = 6 83 + 8 83 = ( 7 1 ) 83 + ( 7 + 1 ) 83 a_{83} = 6^{83} + 8^{83} = (7-1)^{83} + (7+1)^{83}

After simplifying most of the terms will be equivalent to 0 by module 49 and we get:

( 7 1 ) 83 + ( 7 + 1 ) 83 ( 83 82 ) 7 1 + ( 83 82 ) 7 + 1 2 7 83 35 ( m o d 49 ) (7-1)^{83} + (7+1)^{83} \equiv {83 \choose 82}*7 -1 + {83 \choose 82}*7 + 1 \equiv 2*7*83 \equiv 35 \pmod{49}

Since gcd( 6 , 49 6,49 ) = gcd( 8 , 49 8,49 ) = 1 1 , Euler's theorem yields

6 ϕ ( 49 ) 1 6^{\phi(49)}\equiv 1 (mod 49 49 ) and 8 ϕ ( 49 ) 1 8^{\phi(49)}\equiv 1 (mod 49 49 ),

where ϕ ( 49 ) = 49 ( 1 1 7 ) = 42 \phi(49) = 49\left(1-\frac{1}{7}\right) = 42 . Therefore,

( 6 42 ) 2 = 6 84 1 (6^{42})^2 = 6^{84}\equiv 1 (mod 49 49 ) 8 6 84 = 48 6 83 8 \Rightarrow 8\cdot 6^{84} = 48\cdot 6^{83} \equiv 8 (mod 49 49 ) 6 83 8 \Rightarrow 6^{83} \equiv -8 (mod 49 49 ),

and

( 8 42 ) 2 = 8 84 1 (8^{42})^2 = 8^{84}\equiv 1 (mod 49 49 ) 6 8 84 = 48 8 83 6 \Rightarrow 6\cdot 8^{84} = 48\cdot 8^{83} \equiv 6 (mod 49 49 ) 8 83 6 \Rightarrow 8^{83} \equiv -6 (mod 49 49 ).

Combining the last two results we finally obtain

a 83 = 6 83 + 8 83 8 6 a_{83} = 6^{83}+8^{83}\equiv-8-6 (mod 49 49 ) 35 \,\equiv\boxed{35} (mod 49 49 ).

Mahdi Raza
Apr 19, 2020

a 83 = 6 83 + 8 83 = ( 7 1 ) 83 + ( 7 + 1 ) 83 \begin{aligned} a_{83} &= 6^{83} + 8^{83} \\ &= (7-1)^{83} + (7+1)^{83} \end{aligned}

Can be expanded using binomial theorem

\[ \begin{array}{cccccccr} &&\bigg( \binom{83}{0}7^{83}\cdot(-1)^{0} & + \cancel{ \binom{83}{1}7^{82}\cdot(-1)^{1}} &+ \binom{83}{2}7^{81}\cdot(-1)^{2} &+ \cancel{\binom{83}{3}7^{80}\cdot(-1)^{3}} &+ \ldots &+ \binom{83}{82}7^{1}\cdot(-1)^{82} &+ \cancel{\binom{83}{83}7^{0}\cdot(-1)^{83}} \bigg)

\\ &+&\bigg( \binom{83}{0}7^{83}\cdot(1)^{0} &+ \cancel{\binom{83}{1}7^{82}\cdot(1)^{1}} &+ \binom{83}{2}7^{81}\cdot(1)^{2} & + \cancel{\binom{83}{3}7^{80}\cdot(1)^{3}} &+ \ldots &+ \binom{83}{82}7^{1}\cdot(-1)^{82} &+ \cancel{\binom{83}{83}7^{0}\cdot(1)^{83}} \bigg)
\\ \hline \\ &&\bigg( 2 \cdot \binom{83}{0}7^{83}\cdot(-1)^{0} & &+ 2\cdot \binom{83}{2}7^{81}\cdot(-1)^{2} & &+ \ldots &+ 2 \cdot \binom{83}{82}7^{1}\cdot(-1)^{82} &\bigg) \end{array}\]

All the odd powers cancel and twice of even remain. Form that 7 2 \color{#D61F06}{7^2} can be factored out with remainder in Blue \color{#3D99F6}{\text{Blue}}

7 2 ( 2 ( 83 0 ) 7 83 2 ( 1 ) 0 + 2 ( 83 2 ) 7 81 2 ( 1 ) 2 + + 2 ( 83 80 ) 7 3 2 ( 1 ) 82 ) + 2 ( 83 82 ) 7 1 ( 1 ) 82 \implies \color{#D61F06}{7^2} \color{#333333}{\cdot\bigg( 2 \cdot \binom{83}{0}7^{83-2}\cdot(-1)^{0} + 2\cdot \binom{83}{2}7^{81-2}\cdot(-1)^{2} + \ldots + 2 \cdot \binom{83}{80}7^{3-2}\cdot(-1)^{82} \bigg) + \color{#3D99F6}{2 \cdot \binom{83}{82}7^{1}\cdot(-1)^{82}}}

2 ( 83 82 ) 7 1 ( 1 ) 82 = 2 × 83 × 7 × 1 = 1162 35 ( m o d 49 ) \color{#3D99F6}{2 \cdot \binom{83}{82}7^{1}\cdot(-1)^{82 }} \color{#333333}{ = 2 \times 83 \times 7 \times 1 = 1162 \equiv \boxed{\color{#D61F06}{35}}\pmod{49}}

Andy Hayes
Dec 19, 2016

The goal is to compute the residue of:

6 83 + 8 83 ( m o d 49 ) . 6^{83}+8^{83} \pmod{49}.

First, compute ϕ ( 49 ) = 7 2 7 1 = 42. \phi(49)=7^2-7^1=42. Then, apply Euler's Theorem :

6 83 + 8 83 6 41 + 8 41 ( m o d 49 ) . 6^{83}+8^{83} \equiv 6^{41}+8^{41} \pmod {49}.

The residues can be found using the method of repeated squares. Find the binary representation of 41:

4 1 10 = 10100 1 2 . 41_{10}=101001_{2}.

Then compute the residues of the repeated squares:

k 6 2 k ( m o d 49 ) 8 2 k ( m o d 49 ) 0 6 8 1 36 15 2 22 29 3 43 8 4 36 15 5 22 29 \begin{array}{c|c|c} k & 6^{2^k} \pmod{49} & 8^{2^k} \pmod{49} \\ \hline 0 & 6 & 8 \\ 1 & 36 & 15 \\ 2 & 22 & 29 \\ 3 & 43 & 8 \\ 4 & 36 & 15\\ 5 & 22 & 29 \end{array}

Then, simplify the congruence:

6 41 + 8 41 ( 6 2 5 ) ( 6 2 3 ) ( 6 2 0 ) + ( 8 2 5 ) ( 8 2 3 ) ( 8 2 0 ) ( m o d 49 ) ( 22 ) ( 43 ) ( 6 ) + ( 29 ) ( 8 ) ( 8 ) ( m o d 49 ) 41 + 43 ( m o d 49 ) 35 . \begin{aligned} 6^{41}+8^{41} &\equiv \left(6^{2^5}\right)\left(6^{2^3}\right)\left(6^{2^0}\right) + \left(8^{2^5}\right)\left(8^{2^3}\right)\left(8^{2^0}\right) \pmod{49} \\ &\equiv (22)(43)(6)+(29)(8)(8) \pmod{49} \\ &\equiv 41+43 \pmod{49} \\ &\equiv \boxed{35}. \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...